Ridesain Jambur di Desa Sumbul Tema: Arsitektur Neo-Vernakular - Aroli Harefa; Mei Brilian Harefa; Dasrizal Dasrizal (PT PUSTAKA CENDEKIA GROUP, 2026)
The Jambur is a traditional communal building of the Karo community used for social, cultural, and customary activities. Over time, many Jambur buildings have undergone transformations that reduce their traditional architectural characteristics. This condition is also found in the Sumbul Village Jambur, Berastagi District, Karo Regency. This study aims to redesign the Sumbul Village Jambur using a neo-vernacular architectural approach as an effort to preserve local cultural identity. The research employs a qualitative descriptive design method through field observation, literature review, site analysis, spatial requirement analysis, and transformation of traditional Karo architectural elements into contemporary design. The results indicate that neo-vernacular principles are implemented through the use of a rectangular building form, adaptation of traditional Karo roof forms, application of traditional Karo colors, Gerga ornaments, and modern materials representing traditional elements. The redesigned building accommodates approximately 1,200 users with a main hall area of 1,351 m². The neo-vernacular approach successfully preserves Karo cultural identity while fulfilling contemporary functional and structural requirements.